Underestimated diversity in high elevations of a global biodiversity hotspot: two new endemic species of Aethionema (Brassicaceae) from the alpine zone of Iran - Moazzeni, Hamid; Mahmoodi, Mohammad; Jafari, Mohammad; Schneeweiss, Gerald M.; Noroozi, Jalil (Frontiers in Plant Science, 2023)
Although mountains in South-West Asia are a global biodiversity hotspot, our understanding of their biodiversity, especially in the commonly remote alpine and subnival zones, is still limited. This is well exemplified here by Aethionema umbellatum (Brassicaceae), a species considered to have a wide yet disjoint distribution in the Zagros and Yazd-Kerman mountains of western and central Iran. Morphological and molecular phylogenetic data (based on plastid trnL-trnF and nuclear ITS sequences) show that A. umbellatum is restricted to a single mountain range in southwestern Iran (Dena Mts., southern Zagros), whereas populations from central Iran (Yazd-Kerman and central Zagros) and from western Iran (central Zagros) belong to species new to science, A. alpinum and A. zagricum, respectively. Both new species are phylogenetically and morphologically close to A. umbellatum, with which they share unilocular fruits and one-seeded locules. However, they are easily distinguishable by leaf shape, petal size and fruit characters. This study confirms that the alpine flora of the Irano-Anatolian region is still poorly known. As the proportion of rare and local endemic species in alpine habitats is high, these habitats are of prime interest for conservation efforts.